2017
DOI: 10.1021/acs.cgd.7b00467
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of C60 on Rubrene Single Crystals for a Highly Ordered Organic Donor/Acceptor Interface

Abstract: The highly ordered epitaxial growth of C 60 films on rubrene single crystals was demonstrated. The C 60 crystals growth commensurate with rubrene (001) surface lattice was confirmed by reflection high energy electron diffraction and X-ray diffraction and grazing incident wide-angle X-ray scattering. Depending on growth conditions, several surface morphologies (rounded, hexagonal, and triangular grains) of C 60 grains were observed at the initial growth process. Large grains with layer-bylayer step and terrace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…On the other hand, structural analyses have disclosed well-defined assembly of several organic semiconductor molecules via heteroepitaxial growth on molecular single crystal substrates. [243][244][245][246][247][248][249][250] For instance, it was demonstrated by means of surface X-ray diffraction works that n-type semiconductor molecules of C 60 245 and perfluoropentacene (PFP; C 22 F 14 ) 250 form uniquely oriented crystallites on the single crystal surface of pentacene, and the mean size of these epitaxial crystallites reaches the 100 nm order. 246,248 Before closing this article, photoemission analyses conducted on these well-defined molecular-molecular heterointerfaces built on the Pn-SC will be summarized in the following paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, structural analyses have disclosed well-defined assembly of several organic semiconductor molecules via heteroepitaxial growth on molecular single crystal substrates. [243][244][245][246][247][248][249][250] For instance, it was demonstrated by means of surface X-ray diffraction works that n-type semiconductor molecules of C 60 245 and perfluoropentacene (PFP; C 22 F 14 ) 250 form uniquely oriented crystallites on the single crystal surface of pentacene, and the mean size of these epitaxial crystallites reaches the 100 nm order. 246,248 Before closing this article, photoemission analyses conducted on these well-defined molecular-molecular heterointerfaces built on the Pn-SC will be summarized in the following paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…PYS is a suitable methodology for electronic characterization of specimens of low electric conductance [24,25], which is the case for intrinsic rubrene as a wide-gap (2.8 eV [26]) semiconductor, and particularly for detecting small modifications at the highest-occupied electronic states in an extreme sensitivity [27][28][29]. GIXD is a technique for determination of the crystal structures of thin films, and has successfully been applied to hetero-epitaxial organic semiconductor junctions built on molecular single crystals for specification of the lattice orientations [30][31][32] and even for evaluation of their crystallographic qualities by using high-resolution apparatuses [33][34][35]. It was confirmed that homoepitaxial rubrene single crystals grow without any apparent lattice distortion up to the thickness of 100 nm by the present GIXD measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Other organic materials, such as C 60 , or even inorganic materials, such as perovskite films, can also benefit from patterned rubrene acting as templates for epitaxial growth. [64,65] This work demonstrates the potential of RIE in patterning organic crystals without seriously damaging their performance and expands the possibilities for applying organic single crystal in practical electronic devices.…”
Section: Discussionmentioning
confidence: 77%